Physiological Responses to Swimming-Induced Exercise in the Adult Zebrafish Regenerating Heart - Rovira, Mireia; Borràs, Daniel M.; Marques, Inês J.; Puig, Carolina; Planas, Josep V. (Frontiers in Physiology, 2018)
Exercise promotes a set of physiological responses known to provide long-term health benefits and it can play an important role in cardioprotection. In the present study, we examined cardiac responses to exercise training in the adult zebrafish and in the context of cardiac regeneration. We found that swimming-induced exercise increased cardiomyocyte proliferation and that this response was also found under regenerating conditions, when exercise was performed either prior to and after ventricular cryoinjury (CI). Exercise prior to CI resulted in a mild improvement in cardiac function and lesion recovery over the non-exercise condition. Transcriptomic profiling of regenerating ventricles in cryoinjured fish subjected to exercise identified genes possibly involved in the cardioprotective effects of exercise and that could represent potential targets for heart regeneration strategies. Taken together, our results suggest that exercise constitutes a physiological stimulus that may help promote cardiomyogenic mechanisms of the vertebrate heart through the induction of cardiomyocyte proliferation. The zebrafish exercise model may be useful for investigating the potential cardioprotective effects of exercise in teleost fish and to contribute to further identify and develop novel avenues in basic research to promote heart regeneration.